PERSPECTIVES OF PROGRESSIVE WEB APPS - Ritiņš, Arnis; Sergejevs, Aleksejs; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Given the monopoly over native mobile market for certain kind of apps, a cheaper and an easier to make alternative is necessary. One such alternative are the progressive web apps which solve some of the issues related to the native mobile apps. The goal of the work is to analyse the pros of progressive web apps and native mobile apps and estimate why and at which scenarios the progressive web apps can outcompete native mobile apps in terms of the pros.